2021
DOI: 10.1016/j.appet.2021.105244
|View full text |Cite
|
Sign up to set email alerts
|

Relationship in dietary habits variations during COVID-19 lockdown in Kosovo: The COVIDiet study

Abstract: Changes in dietary habits and association with lifestyle during the coronavirus disease 2019 (COVID-19) lockdown in the Kosovo population have not been studied yet. Therefore, the intent of the present study was to determine whether if COVID-19 lockdown had any impact in lifestyle, including dietary habits and physical activity (PA) patterns of people from different areas of Kosovo. Dietary habits, PA, body weight and sociodemographic variables were measured through validated online survey started one week aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 27 publications
1
14
0
3
Order By: Relevance
“…Research indicates the COVID-19 pandemic significantly affected lifestyle, particularly reducing physical activity and changing eating habits [10][11][12][13][14][15][16][17][18][19][20]. Sulejmani et al [20] found that the weight gained during the lockdown in Kosovo was positively associated with a higher cooking frequency, lower meat and fish consumption, higher fast-food consumption, and no physical activity performance. The study results from Iraqi Kurdistan showed that 12.0% of participants reported improvements in lifestyle, whereas 50.9% declared that their lifestyle deteriorated [16].…”
Section: Orthorexia Fear Of Covid-19 and Pa Among University Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research indicates the COVID-19 pandemic significantly affected lifestyle, particularly reducing physical activity and changing eating habits [10][11][12][13][14][15][16][17][18][19][20]. Sulejmani et al [20] found that the weight gained during the lockdown in Kosovo was positively associated with a higher cooking frequency, lower meat and fish consumption, higher fast-food consumption, and no physical activity performance. The study results from Iraqi Kurdistan showed that 12.0% of participants reported improvements in lifestyle, whereas 50.9% declared that their lifestyle deteriorated [16].…”
Section: Orthorexia Fear Of Covid-19 and Pa Among University Studentsmentioning
confidence: 99%
“…The COVID-19 pandemic significantly impacted lifestyle, including changes in dietary habits and physical activity (PA) patterns [10][11][12][13][14][15][16][17][18][19][20]. Izzo et al [17] found changes in eating habits among 33.5% of respondents (out of which 81% reported an increase in frozen food consumption) and physical activity reduction in 70.5% of the Italian population during the COVID-19 lockdown.…”
Section: Introduction 1impact Of Covid-19 On Lifestylementioning
confidence: 99%
“…Exercise in quarantine led to better nutritional choices which in turn had a beneficial effect on mental state as well [ 63 ]. However, it is important to emphasize that exercise frequency has been repeatedly reported to decrease during the pandemic [ 57 , 59 ] The poor nutritional behaviour and lack of exercise have resulted in predictable and unhealthy increases in weight gain during the pandemic [ 64 , 65 ]. These changes in dietary habits have important implications for the health impact of the pandemic.…”
Section: Changes In Dietary Behaviour During the Pandemic And Their Consequencesmentioning
confidence: 99%
“…This is significant because COVID-19-related calls to the Alberta 211 Helpline showed food was one of the top, unmet basic needs of Albertans during the lockdown beginning in March 2020 [ 19 ]. Studies from Europe indicate some improvements in dietary habits (e.g., higher Mediterranean diet score) during lockdown [ 20 , 21 , 22 , 23 ] coupled paradoxically with weight gain, perhaps due in part to enforced physical inactivity and increased snacking [ 20 , 24 ] but these studies had few older adults and did not stratify the results by age. The NutriQuébec study conducted in Canada found a 1.1-point increase in the Healthy Eating Index-2015 in adults, comparing April–May 2020 to June 2019–March 2020.…”
Section: Introductionmentioning
confidence: 99%